(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Pyrene (C16H10) is an organic semiconductor which has wide applications in the field of organic electronics suitable for the development of organic light emitting diodes (OLED) and organic photovoltaic cells (OPV). In this work, Density Functional Theory (DFT) using Beckeâ€™s three and Lee Yang Parr (B3LYP) functional with basis set 6-311++G(d, p) implemented in Gaussian 03 package was used to compute total energy, bond parameters, HOMO-LUMO energy gap, electron affinity, ionization potential, chemical reactivity descriptors, dipole moment, isotropic polarizability (Î±), anisotropy of polarizability ( Î”âˆ) total first order hyper-polarizability () and second order hyperpolarizability (). The molecules used are pyrene, 1-chloropyrene and 4-chloropyrene in gas phase and in five different solvents: benzene, chloroform, acetone, DMSO and water. The results obtained show that solvents and chlorination actually influenced the properties of the molecules. The isolated pyrene in acetone has the largest value of HOMO-LUMO energy gap of and is a bit closer to a previously reported experimental value of and hence is the most stable. Thus, the pyrene molecule has more kinetic stability and can be described as low reactive molecule. The calculated dipole moments are in the order of 4-chloropyrene (1.7645 D) < 1-chloropyrene (1.9663 D) in gas phase. The anisotropy of polarizability ( for pyrene and its derivatives were found to increase with increasing polarity of the solvents. In a nutshell, the molecules will be promising for organic optoelectronic devices based on their computed properties as reported by this work.